Xanthine oxidase inhibitor febuxostat reduces atrial fibrillation susceptibility by inhibition of oxidized CaMKII in Dahl salt-sensitive rats. Issue 20 (29th October 2021) - Xu, DongZhu; Murakoshi, Nobuyuki; Tajiri, Kazuko; Duo, Feng; Okabe, Yuta; Murakata, Yoshiko; Yuan, Zixun; Li, Siqi; Aonuma, Kazuhiro; Song, Zonghu; Shimoda, Yuzuno; Mori, Haruka; et al.
Abstract: Oxidative stress could be a possible mechanism and a therapeutic target of atrial fibrillation (AF). However, the effects of the xanthine oxidase (XO) inhibition for AF remain to be fully elucidated. We investigated the effects of a novel XO inhibitor febuxostat on AF compared with allopurinol in hypertension rat model. Five-week-old Dahl salt-sensitive rats were fed either low-salt (LS) (0.3% NaCl) or high-salt (HS) (8% NaCl) diet. After 4 weeks of diet, HS diet rats were divided into three groups: orally administered to vehicle (HS-C), febuxostat (5 mg/kg/day) (HS-F), or allopurinol (50 mg/kg/day) (HS-A). After 4 weeks of treatment, systolic blood pressure (SBP) was significantly higher in HS-C than LS, and it was slightly but significantly decreased by treatment with each XO inhibitor. AF duration was significantly prolonged in HS-C compared with LS, and significantly suppressed in both HS-F and HS-A (LS; 5.8 ± 3.5 s, HS-C; 33.9 ± 23.7 s, HS-F; 15.0 ± 14.1 s, HS-A; 20.1 ± 11.9 s: P <0.05). Ca 2+ spark frequency was obviously increased in HS-C rats and reduced in the XO inhibitor-treated rats, especially in HS-F group. Western blotting revealed that the atrial expression levels of Met 281/282 -oxidized Ca 2+ /Calmodulin-dependent kinase II (CaMKII) and Ser 2814 -phosphorylated ryanodine receptor 2 were significantly increased in HS-C, and those were suppressed in HS-F and HS-A. Decreased expression of gap junction protein connexin 40 in HS-C was partially restored by treatment with each XO inhibitor. In conclusion, XO inhibitor febuxostat, as well as allopurinol, could reduce hypertension-related increase in AF perpetuation by restoring Ca 2+ handling and gap junction.